The Lyricism of the Generation of '27 in the Songs of Carlos Morla Lynch (1933-1938) (Anclajes, 2026)
2027 marks the centenary of the Generation of '27. In light of this event, the songs that Chilean diplomat Carlos Morla Lynch composed based on poems by members of this group, many of whom were his friends and frequented the literary gatherings held at his home, will be published for the first time in Spain. This article analyzes the circumstances in which these songs were made and describes the musical production of Carlos Morla between 1933 and 1938.
Keywords: Poetry set to music; Generation of '27; Federico García Lorca; Carlos Morla Lynch